THE EFFECTS OF TEACHING TECHNIQUES ON STUDENTS’ SPEAKING SKILL AT JUNIOR HIGH SCHOOL IN CIREBON, WEST JAVA - Supriyani, Supriyani (Universitas Wiralodra, 2018)
The purpose of this study was to determine the interactional effects of teaching techniques on students? speaking skill, that was taught by role play and filling information gap (both are communicative language teaching) to the students. The research method used was experimental one. Sample size of 60 students consist of 30 for experimental class and 30 for control class taken from SMP 15 and SMP 16 in Cirebon, West Java, and the sampling technique is cluster sampling. Research instrument used was the test and the result of speaking skill in the form of oral test (5 items), has been tested valid and reliable with coefficient of reliability at 0.732. The result showed. There is a significant effect of teaching techniques on students? speaking skill, as Fobserved = 2.833 and sig = 0.014 < 0.05.